The Internet of Things 20th Tyrrhenian Workshop on Digital Communications - Giusto, Daniel.; Giusto, Daniel.; Iera, Antonio.; Iera, Antonio.; Morabito, Giacomo.; Morabito, Giacomo.; Atzori, Luigi.; Atzori, Luigi. (Springer New York : Imprint: Springer, 2010)
This book presents a selection of papers submitted to the 20th Tyrrhenian Workshop, which took place in September 2009 in Sardinia, Italy. The workshop focused on the "Internet of Things." This subject is quickly emerging in the wireless technology arena. It describes the pervasive presence of a variety of devices—such as sensors, actuators, and mobile phones—which, through unique addressing schemes, are able to interact and cooperate with each other to reach common goals. This novel paradigm, which originated from the idea of "smart" environments, will be sure to impact the future of logistics, Intelligent Transportation Systems, business and process management, assisted living, E-health, and other applications. The Internet of Things covers a wide array of essential topics related to this emerging paradigm, including infrastructures and applications, communication systems and network architectures, embedded systems, and location and tracking through navigation sensors. It also addresses the technological and social implications of this technology, as well as challenges that may arise.